2009
DOI: 10.1523/jneurosci.3827-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Adult Rat Retinal Ganglion Cells by D1-Type Dopamine Receptor Activation

Abstract: The spike output of neural pathways can be regulated by modulating output neuron excitability and/or their synaptic inputs. Dopaminergic interneurons synapse onto cells that route signals to mammalian retinal ganglion cells, but it is unknown whether dopamine can activate receptors in these ganglion cells and, if it does, how this affects their excitability. Here, we show D1a-receptor-like immunoreactivity in ganglion cells identified in adult rats by retrogradely transported dextran, and that dopamine, D1-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 116 publications
3
40
2
Order By: Relevance
“…Curiously, both D1 and D2 receptor antibodies, ligands, and mRNA probes bind to the mammalian retinal ganglion cell layer (Brann and Young, 1986; Cohen et al, 1992; Wagner et al, 1993; Bjelke et al, 1996; Veruki and Wassle, 1996; Hayashida et al, 2009; Van Hook et al, 2012). Whereas this could reflect mixtures of cells expressing either D1 or D2 receptors, dopamine responses in other preparations are known to involve more than one receptor subtype and, in some cases, different signaling cascades and heteromeric receptor complexes (Neve et al, 2004; Hasbi et al, 2010).…”
mentioning
confidence: 99%
“…Curiously, both D1 and D2 receptor antibodies, ligands, and mRNA probes bind to the mammalian retinal ganglion cell layer (Brann and Young, 1986; Cohen et al, 1992; Wagner et al, 1993; Bjelke et al, 1996; Veruki and Wassle, 1996; Hayashida et al, 2009; Van Hook et al, 2012). Whereas this could reflect mixtures of cells expressing either D1 or D2 receptors, dopamine responses in other preparations are known to involve more than one receptor subtype and, in some cases, different signaling cascades and heteromeric receptor complexes (Neve et al, 2004; Hasbi et al, 2010).…”
mentioning
confidence: 99%
“…Likewise, we have found that a mouse monoclonal antibody against D1 dopamine receptors (clone SG2-D1a; cat# NB110-60017; Novus Biologicals) also stains rat retinal ganglion cell somata (Fig. 2M–P; see also Hayashida et al, 2009) and a subsequent study (Van Hook et al, 2012) found similar binding of a polyclonal anti-D1a receptor antibody in rat retina. The monoclonal antibody bound to a protein band of the estimated molecular weight expected of D1a receptors (e.g., Huang et al, 1992) in western blots of whole retinal homogenate.…”
Section: Formaldehydementioning
confidence: 65%
“…Scale bar in (P) is 20 µm and applies to (D,H,L,P). Lack of detectable GCL immunopositivity in A–L contrasts with GCL immunopositivity in M–P and with ganglion cell dopamine-sensitivity (Hayashida et al, 2009; Ogata et al, 2012). …”
Section: Figurementioning
confidence: 86%
See 2 more Smart Citations